Political finance regimes, political corruption and party system institutionalization in Southeast Asia - Croissant, Aurel (Political corruption and organizational crime, 2021)
It is a long-standing belief in democracy studies that configurations of well-institutionalized and both moderately polarized and fractionalized party systems promote the effectiveness and efficiency of democratic institutions and thereby contribute to the functioning and legitimacy of the democratic system at large. At the same time, scholars frequently reassert the difficulty of consolidating democracy if political parties and party systems fail to establish a strong institutional linkage with society. The chapter analyses these issues in the context of Southeast Asia.
Gesehen am 17.12.2021